Selection of exercises for physical development for first-year male students of Duy Tan University in Danang, Viet Nam - Xuan Hung , Nguyen; Anh Khoa, Nguyen Huu (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
This study aimed to select and evaluate exercises for the physical development of first-year male students at Duy Tan University in Da Nang, Vietnam. Utilizing an experimental design, documentary analysis, interviews, and pedagogical testing, the study involved 32 experienced physical education lecturers to ensure exercise reliability. The experimental phase included 46 first-year male students, who were divided into two groups: a control group (n = 23) following the standard curriculum and an experimental group (n = 23) incorporating 19 additional exercises categorized into five groups: rapid strength development (4 exercises), strength development (6 exercises), endurance (4 exercises), flexibility (3 exercises), and dexterity (4 exercises). Over five months, both groups attended 36 classes. Statistical analysis revealed significant differences between the groups (p < 0.05), indicating that the experimental group showed notable improvements in physical fitness due to the newly selected exercises. As a result, the selected exercises were highly effective in developing the physical fitness of first-year male students at Duy Tan University in Da Nang, Vietnam.